Aplikasi Monitoring Kelembapan Tanah, Suhu, Kadar PH Tanah Serta Penyiraman Dan Pemupukan Otomatis Pada Tanaman Hias Lidah Mertua Berbasis IOT - Winsen Winsen; Alexander Setiawan; Resmana Lim (Universitas Kristen Petra, 2022)
The maintenance of mother-in-law's tongue ornamental plants often makes mistakes because ornamental plants have many types of plants. Some ornamental plants such as mother-in-law's tongue have a quite different handling compared to most of the existing ornamental plants such as air requirements around 5-8% while most ornamental plants require 50-70%.The problem that the author wants to solve is by utilizing android and IoT applications which function to monitor the mother-in-law's tongue ornamental plants and provide adequate watering and fertilization.The test was carried out using 4 ornamental plants that were treated with different treatments. From the results of the tests carried out, the application that was made was able to monitor and control the water and fertilizer content accurately and the results from the test method were able to achieve an accuracy value of 100%.